Pengaruh Aplikasi Smart Kampung Banyuwangi Terhadap Kualitas Pelayanan Administrasi Kependudukan di Dinas Kependudukan dan Pencatatan Sipil (DISDUKCAPIL) Kabupaten Banyuwangi - Thania Puspa Candrika Putri Aji; Lilik Antarini; I Wayan Sudemen (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2024)
The implementation of electronic government is part of an effort to improve the quality of public services. The implementation of electronic government in Indonesia is currently not running optimally because there are still a number of challenges and obstacles. Banyuwangi Regency through the Smart Kampung Banyuwangi application also hopes for better changes in terms of service quality, but in its implementation there are still obstacles in using the Smart Kampung Banyuwangi application as a means of accessing services. The research focuses on knowing the effect of the Smart Kampung Banyuwangi application on the quality of population administration services at the Population and Civil Registration Office of Banyuwangi Regency. Previous research related to Smart Kampung Banyuwangi, no one has discussed the effect of the Smart Kampung Banyuwangi application on service quality, so research needs to be done to find out whether the use of the Smart Kampung Banyuwangi application is in accordance with the purpose of creating the system so that further efforts can be formulated in using the Smart Kampung Banyuwangi application. The research includes aspects of system security, accuracy of documents produced, design, ease of use, social involvement, and the opportunity for the community to assess the performance of the application system, so as to complement aspects that have not been studied in previous studies. The research was conducted using quantitative methods, with data collection techniques through observation, questionnaires, and documentation. The data analysis process was carried out through descriptive statistical techniques and inferential statistics. The analytical test tools used include validity, reliability, product moment correlation, simple linear regression, and coefficient of determination analysis using SPSS version 25. Based on the results of the correlation test, a correlation value of 0.827 was obtained, indicating a very strong level of relationship between the Smart Kampung Banyuwangi application and the quality of population administration services. The results of the simple linear regression analysis test obtained the regression equation Y = 3.543 + 0.908X which shows a positive and significant influence between the Smart Kampung Banyuwangi application on the quality of population administration services. The results of the coefficient of determination analysis obtained an R^2 value of 0.685, indicating the magnitude of the influence of the Smart Kampung Banyuwangi application on the quality of population administration services by 68.5%. Thus the hypothesis that there is a positive and significant influence between the Smart Kampung Banyuwangi application on the quality of population administration services at the Population and Civil Registration Office of Banyuwangi Regency can be accepted.